2017
DOI: 10.1002/2017ja024392
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sudden Stratospheric Warming of 2009 on the Equatorial and Low‐Latitude Ionosphere of the Indian Longitudes: A Case Study

Abstract: Using the equatorial electrojet (EEJ)‐induced surface magnetic field and total electron content (TEC) measurements, we investigated the impact of the sudden stratospheric warming (SSW) of January 2009 on the equatorial electrodynamics and low‐latitude ionosphere over the Indian longitudes. Results indicate that the intensity of EEJ and the TEC over low latitudes (extending up to 30°N) exhibit significant perturbations during and after the SSW peak. One of the interesting features is the deviation of EEJ and TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Fejer et al (2010) suggested that this signature in the EEJ could be linked to the enhancements of the lunar semidiurnal tide (M2). Since then, a number of studies have confirmed their findings using magnetic observations from satellite (e.g., Park et al, 2012) and ground-based observatories (e.g., Yamazaki et al, 2012;Yamazaki, 2013;Sathishkumar and Sridharan, 2013;Siddiqui et al, 2017;Yadav et al, 2017).…”
Section: Introductionmentioning
confidence: 85%
“…Fejer et al (2010) suggested that this signature in the EEJ could be linked to the enhancements of the lunar semidiurnal tide (M2). Since then, a number of studies have confirmed their findings using magnetic observations from satellite (e.g., Park et al, 2012) and ground-based observatories (e.g., Yamazaki et al, 2012;Yamazaki, 2013;Sathishkumar and Sridharan, 2013;Siddiqui et al, 2017;Yadav et al, 2017).…”
Section: Introductionmentioning
confidence: 85%
“…Fejer et al (2010) reported that such semidiurnal perturbations are the result of the enhanced semidiurnal lunar tide and it was mostly consistent with the results of Pedatella and Forbes (2010). Yadav et al (2017) showed the deviation in EEJ and TEC from the normal behavior simultaneously with the enhancement in PW 2 before the onset of the 2009 SSW event. Similar TEC behavior is also observed in the present study at low latitude stations.…”
Section: Discussionmentioning
confidence: 99%
“…The behavior of the EEJ, CEJ, and TEC before, during, and after the SSW events has been studied extensively during the past (Chau et al, ; Sathishkumar & Sridharan, ; Vineeth et al, ; Yadav et al, , and references therein). The novelty of the results presented in this study is the characteristic difference in the response of low‐latitude ionosphere to the SSW events occurred in different phases of the QBO.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, during the SSWs, significant changes have been observed in ionosphere‐thermosphere system associated with the enhancement in solar and lunar semidiurnal tides (Fang et al, ; Pedatella & Liu, ). It has also been shown that the tidal changes associated with the global circulation can influence the energetics and electrodynamics of the MLT region much before the onset of the SSW, as preconditioning (Vineeth et al, ; Yadav et al, ).…”
Section: Introductionmentioning
confidence: 99%